Analisis Struktur Analytical Exposition Text dalam Tajuk Rencana Surat Kabar Harian Analisa - febriyanti yustisia simbolon (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
This study aims to describe the analysis of the analytical exposition text structure in the editorial of a daily newspaper analysis.This study used descriptive qualitative method. The source of the data is daily editorial analysis for the months of July, August, and September 2021. The data collection technique in this study is a literature study by collecting literature sources. The data analysis technique used in this study is data that has been collected by researchers from data sources. In the data analysis, the researcher uses data analysis with data reduction methods (data reduction), data presentation (data display) and conclusions (verification) in Sugiyono (2017:247-252). Data reduction method (data reduction) is a form of analysis that sharpens, categorizes, directs, discards unnecessary, and organizes data in such a way that the final conclusions can be examined and verified. Phase of presenting data (data display) is an activity of making research results that have been carried out so that the data collected can be understood and analyzed in accordance with the desired goals. The conclusion (verification) is the idea reached at the end or the result of the conversation.Thus, the analytical exposition text structure in the daily newspaper editorial analysis proves that the editorial can be analyzed based on structure and language so that the editorial reader can understand more deeply about the problems that occur.